Myeloid neoplasms after chemotherapy and PRRT: myth and reality. Issue 8 (August 2016) - Bodei, Lisa; Modlin, Irvin M; Luster, Markus; Forrer, Flavio; Cremonesi, Marta; Hicks, Rodney J; Ezziddin, Samer; Kidd, Mark; Chiti, Arturo
Abstract : Peptide receptor radionuclide therapy (PRRT) with 90 Y-octreotide or 177 Lu-octreotate is an effective treatment for inoperable or metastatic neuroendocrine tumors (NETs), particularly well-differentiated gastroenteropancreatic or bronchopulmonary NETs. PRRT is generally extremely well tolerated, with modest toxicity to target organs, kidney and bone marrow. Nevertheless, a priori concerns regarding long-term effects lead clinicians such as Brieau and coworkers, in this ERC issue, to ascribe to the combination of alkylating agents and PRRT the apparently high occurrence ( n =4) of myeloproliferative events (therapy-related myeloid neoplasms (t-MNs)) in a small cohort of 20 progressive, advanced digestive NETs treated with PRRT after chemotherapy. Anecdotal reports of myelotoxic events should be placed in the correct perspective of larger series, where the reported incidence of these events is 2%, with the aim of promoting a balanced awareness of the issue and unbiased and reasonable overall conclusions. For a comprehensive definition of the issue, we provide an evaluation of the occurrence of t-MN in patients treated with various myelotoxic treatments.